KORELASI LINGKAR SKROTUM TERHADAP KUANTITAS DAN KUALITAS SEMEN PEJANTAN SAPI SIMMENTAL di BALAI BESAR INSEMINASI BUATAN SINGOSARI KABUPATEN MALANG - Risky putri Mareta anwar; Resti Yuliana Rahmawati; Alfan Setya Winurdana (Universitas Islam Balitar, 2022)
This study aims to find out whether there is a correlation between scrotal circumference to the quantity and quality of Simmental cow semen at the Singosari Malang Artificial Insemination Center. The sample used in the form of fresh cement simmental cows amounted to 16 heads. The variables observed are scrotal circumference, semen volume, pH, spermatozoa concentration, spermatozoa motility, and spermatozoa abnormalities. The data analyzed using Ms. Excel, and showed a correlation between scrotal circumference and cement volume r = 0,6943, scrotal circumference with pH r = 0,1645, scrotal circumference with spermatozoa concentration r = -0,3029, scrotal circumference with spermatozoa motility r = -0,1155, scrotal circumference with spermatozoa r = -0,1642 abnormality. Thus, there is a strong correlation between scrotal circumference and semen volume, a very low correlation between scrotal circumference and pH, and there is no scrotal circumference correlation between spermatozoa concentration, spermatozoa motility, and spermatozoa abnormality.